Does physical activity change following hip and knee replacement? Matched case-control study evaluating Physical Activity Scale for the Elderly data from the Osteoarthritis Initiative. Issue 1 (March 2018) - Smith, T.O.; Mansfield, M.; Dainty, J.; Hilton, G.; Mann, C.J.V.; Sackley, C.M.
Abstract: Objectives: To determine whether physical activity measured using the Physical Activity Scale for the Elderly (PASE), changes during the initial 24 months post-total hip (THR) or knee replacement (TKR), and how this compares to a matched non-arthroplasty cohort. Design: Case-controlled study analysis of a prospectively collected dataset. Setting: USA community-based. Participants: 116 people post-THR, 105 people post-TKR compared to 663 people who had not undergone THR or TKR, or had hip or knee osteoarthritis. Cohorts were age-, gender- and BMI-matched. Main outcome measures: Physical activity assessed using the 12-item PASE at 12 and 24 months post operatively. Results: There was no significant difference in total PASE score between pre-operative to 12 months (mean: 136 vs 135 points; p = 0.860) or 24 months following THR (mean: 136 vs 132 points; p = 0.950). Whilst there was no significant difference in total PASE score from pre-operative to 12 months post-TKR (126 vs 121 points; p = 0.930), by 24 months people following TKR reported significantly greater physical activity (126 vs 142 points; p = 0.040). There was no statistically significant difference in physical activity between the normative matched and THR (p ≥ 0.140) or TKR (p ≥ 0.060) cohorts at 12 or 24 months post joint replacement. Conclusions: Physical activity is not appreciably different to pre-operative levels at 12 or 24 months post-THR, but was greater at 24 months following TKR. Health promotion strategies are needed to encourage greater physical activity participation following joint replacement, and particularly targeting those who undergo THR.